Leonurine Attenuates Obesity-Related Vascular Dysfunction and Inflammation - Xiao-Dong Shi; Jia-Xin Zhang; Xi-De Hu; Tao Zhuang; Ning Lu; Cheng-Chao Ruan (MDPI AG, 2022)
Oxidative stress in adipose tissue is a crucial pathogenic mechanism of obesity-associated cardiovascular diseases. Chronic low-grade inflammation caused by obesity increases ROS production and dysregulation of adipocytokines. Leonurine (LEO) is an active alkaloid extracted from Herba Leonuri and plays a protective role in the cardiovascular system. The present study tested whether LEO alleviates inflammation and oxidative stress, and improves vascular function in an obese mouse model. Here, we found that obesity leads to inflammation and oxidative stress in epididymal white adipose tissue (EWAT), as well as vascular dysfunction. LEO significantly improved inflammation and oxidative stress both in vivo and in vitro. Obesity-induced vascular dysfunction was also improved by LEO as evidenced by the ameliorated vascular tone and decreased mesenteric artery fibrosis. Using mass spectrometry, we identified YTHDF1 as the direct target of LEO. Taken together, we demonstrated that LEO improves oxidative stress and vascular remodeling induced by obesity and targets YTHDF1, raising the possibility of LEO treating other obesity-related metabolic syndromes.